Evidence of Validity for the Hierarchical Job Crafting Scale in Brazil. - Branco Brasil, Filipi Junger; David Gabardo-Martins, Larissa Maria (Paideia (0103863X), 2023)
Job crafting is characterized by worker's proactive behavior aiming to give meaning and significance to their work relations, allowing the individual to assume a leading role by acting as an agent of change. The study aimed to gather evidence of validity for the Job Crafting Hierarchical Scale in Brazil. Study sample consisted of 675 Brazilian workers of both genders, aged between 18 and 82 years. Confirmatory Factor Analysis pointed out that the 18-item model, divided into four reflective factors (increase in resources, increase in challenging demands, reduction in demands, and optimization of demands) and one formative factor (job crafting) presented the best adjustment indexes. Results showed a positive correlation with work engagement and a negative correlation with work exhaustion. In conclusion, the instrument presented psychometric properties that recommend its use in future investigations on job crafting in the Brazilian context.